2002
DOI: 10.1115/1.1459471
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Modeling and Characterization of the Curing Process of Underfill Materials

Abstract: Thermo-setting polymers are widely used as underfill materials to improve the reliability of electronic packages. In the design phase, the influence of underfill applications on reliability is often judged through thermal and mechanical simulations, under assumed operating conditions. Because of lacking insight into the mechanical processes due to polymer curing, the impact of processing induced residual stress fields is often neglected. To investigate the evolution of stress and strain fields during the curin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…In processes that glue electronic components to plates, shrinkage-and/or temperature-induced stresses can lead to damage or even to failure of either the adhesive layer or the whole component [2,5]. Recent research has demonstrated that a careful selection of processing parameters dramatically reduces warpage which suggests that process modelling can be a powerful tool for determining optimal curing conditions [6].…”
Section: Previous Workmentioning
confidence: 99%
“…In processes that glue electronic components to plates, shrinkage-and/or temperature-induced stresses can lead to damage or even to failure of either the adhesive layer or the whole component [2,5]. Recent research has demonstrated that a careful selection of processing parameters dramatically reduces warpage which suggests that process modelling can be a powerful tool for determining optimal curing conditions [6].…”
Section: Previous Workmentioning
confidence: 99%
“…Furthermore, they [5] extracted a full cure dependent viscoelastic model for the shear modulus of a commercial molding compound by monitoring the changes in the viscoelastic properties of the compounds during cure. A cure-dependent viscoelastic model was also proposed [6][7][8][9] to describe the evolution of the viscoelastic behavior of an underfill resin in a flip chip package during isothermal and non-isothermal cure.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed description about the model and the experimental methodology can be found in [8]- [10].…”
Section: Modeling Cure-dependent Viscoelastic Behavior Of Underfimentioning
confidence: 99%
“…The temperature dependent Young's modulus is given by [13] (9) where is the temperature in . The yield behavior is described by the following equation [14]: (10) where is the absolute temperature . The creep behavior is described as [13] (11) where equivalent creep strain rate; equivalent stress; Young's modulus; activation energy; universal gas constant; absolute temperature; material constant.…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation